Fabrication of Sb2S3 thin films by sputtering and post-annealing for solar cells. Issue 3 (15th February 2019) - Gao, Chunhui; Huang, Jialiang; Li, Huangxu; Sun, Kaiwen; Lai, Yanqing; Jia, Ming; Jiang, Liangxing; Liu, Fangyang
Abstract: The semiconductor antimony sulfide (Sb2 S3 ) is a potential absorber materials for the top sub-cell of Si-based tandem solar cells because of its appropriate band-gap, simple binary composition, nontoxic elements, and long-term stability. In this study, polycrystalline Sb2 S3 films were fabricated by post-annealing of radio frequency (RF) magnetron sputtered precursors using an Sb2S3 target. The effects of the post-annealing temperature and atmosphere on Sb2 S3 film properties and device performances were investigated. A high-performance device having a 2.41% power conversion efficiency was obtained by making use of a uniform Sb2S3 absorber layer. This preliminary experimental study shows that Sb2S3 thin films could be used as top sub-cell absorber materials for third-generation high efficiency, stable, and environmentally friendly Sb2 S3 /Si tandem solar cells. Graphical abstract: fx1